BIOCHEMICAL STUDIES AND SERODIAGNOSIS OF HAEMONCHOSIS IN SHEEP AND GOATS - GOATS M. F. Qamar; A. Maqbool (Journal of Animal and Plant Sciences, 2012)
Haemonchosis is a serious health problem which causes lower production due to high morbidity, mortality, and cost of treatment and control measures. Therapeutical trials to control and treat haemonchosis were conducted by using various allopathic, homeopathic, herbal and biological products. A total of 120 sheep and goats were randomly divided into groups A, B, C, D, E & F and animals in group A, B, C and D were treated with Ivermectin, Azedarachta indica (neem Leaves) Powder, Trematox (a homeopathic drug), EM-Biovet (Effective micro-organisms) respectively. Whereas E and F were kept as infected untreated and uninfected control respectively. A total of 264 sheep and goat out of 300 blood samples (88%) were found positive for the Haemonchuscontortus. A range of haematological measures were significantly different between infected groups and uninfected controls at one or more time points. The concentrations of serum albumin, packed cells volume (PCV), Erythrocyte sedimentation rate (ESR), blood eosinophil number were significantly increased (P<0.05), while the concentration haemoglobin, total RBCs,total serum proteins, Albumin Globulin Ratio (A/G Ratio) were significantly decreased (P<0.05) in haemonchus infected animals. There were no significant differences among infected and control groups in total WBC counts, but it was relatively high in infected animals compared to healthy animals. The percentage of neutrophils was low while lymphocytes count, number of basophils and monocytes number in percentage were high. It was concluded that decreased hemoglobin concentration, total serum proteins, total RBCs, and A/G ratio were important indicators of haemonchosis in sheep and goats.
Keywords: Haemonchosis; Haemonchus contortus; ELISA; sheep; goats; Pakistan.